2021
DOI: 10.3389/fcell.2020.589985
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of miRNAs in Health and Disease of Retinal Pigment Epithelium

Abstract: MicroRNAs (miRNAs), a class of non-coding RNAs, are essential key players in the control of biological processes in both physiological and pathological conditions. miRNAs play important roles in fine tuning the expression of many genes, which often have roles in common molecular networks. miRNA dysregulation thus renders cells vulnerable to aberrant fluctuations in genes, resulting in degenerative diseases. The retinal pigment epithelium (RPE) is a monolayer of polarized pigmented epithelial cells that resides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 137 publications
0
8
0
Order By: Relevance
“…MicroRNAs play an important role in regulating the development of AMD. [ 47 ] In vivo studies found that dysregulated miRNAs might affect AMD progression by targeting genes involved in neurodegeneration and inflammation. [ 48 ] As senescent cells cause inflammation by senescence-associated secretory phenotype, miRNAs that inhibit inflammation could be effective in the treatment of AMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs play an important role in regulating the development of AMD. [ 47 ] In vivo studies found that dysregulated miRNAs might affect AMD progression by targeting genes involved in neurodegeneration and inflammation. [ 48 ] As senescent cells cause inflammation by senescence-associated secretory phenotype, miRNAs that inhibit inflammation could be effective in the treatment of AMD.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs play an important role in regulating the development of AMD [47] . In vivo studies found that dysregulated miRNAs might affect AMD progression by targeting genes involved in neurodegeneration and inflammation [48] .…”
Section: Discussionmentioning
confidence: 99%
“…This effect is accompanied by a reduction in VEGF-induced ROS synthesis by RPE cells, neovascularization, and the EMT of RPE cells [ 357 ]. MiR-146a, activated in the RPE and choroid during cellular senescence, decreases VEGF activity in RPE cells [ 358 , 359 ]. MiR-93 and miR-302d inhibit the TGFβ signaling pathway and can be considered as a potential approach to prevent TGFβ2-mediated RPE conversion in mesenchymal transformation [ 360 ].…”
Section: The Exogenous Regulation Of Redox Homeostasis Of Rpe Cellsmentioning
confidence: 99%
“…It absorbs light and protects the retina from photooxidation; in addition, it is responsible for stabilizing the concentration of ions in the subretinal space to keep the photoreceptors excitable. To maintain RPE homeostasis and function, a particular molecular network is necessary, with microRNAs being indispensable components [ 94 ].…”
Section: Ocular Neurodegenerative Diseasesmentioning
confidence: 99%